Endogenous market structures and labour market dynamics - Andrea Colciago; Lorenza Rossi (Bank of Finland, 2011)
We propose a flexible prices model where endogenous market structures and search and matching frictions in the labour market interact endogenously. The interplay between firms endogenous entry, strategic interactions among producers and labour market frictions represents a strong amplification channel for technology shocks on labour market variables and helps in addressing the unemployment- volatility puzzle. Consistently with US evidence, new firms create a large fraction of new jobs and grow faster than more mature firms, net entry of firms is procyclical and the price mark-up is countercyclical.
URN:NBN:fi:bof-20140807259
Keywords: 330